A CASE OF TRIPTORELIN-INDUCED THYROIDITIS - Borhan, Marisa Khatijah; Vethakkan, Shirenee Ratna; Ratnasingam, Jeyakantha; Paramsivam, Sharmila Sunita (Journal of the ASEAN Federation of Endocrine Societies, 2023)
INTRODUCTION/BACKGROUND Gonadotrophin-releasing hormone agonists (GnRHa) therapy has been associated with thyroid dysfunction, including thyroiditis. Triptorelin, a GnRHa, is used as androgen deprivation therapy (ADT) in men with prostate cancer. We present a case of triptorelin-induced thyroiditis in a patient with locally advanced prostate cancer. CASE An 83-year-old male with underlying stable prostate cancer presented with an acute transient episode of abnormal behaviour. After completed radiotherapy, he was on 3-monthly SC leuprorelin before recently changing to 3-monthly SC triptorelin. He had received the second dose of SC triptorelin 4 weeks prior to presentation. A plain brain CT ruled out a space-occupying lesion. His renal profile, serum calcium, glucose and dementia workup were normal, except for a deranged TFT [suppressed TSH (0.01 mIU/L, N:0.55-4.78), high fT4 (55.1 pmolL, N:11.5- 22.7), high fT3 (13.0 pmol/L, N:3.5-6.5)]. Baseline TFT taken two years ago was normal. He had no fever, neck pain, dysphagia, respiratory or thyrotoxicosis symptoms. He denied any family history of thyroid disease, recent vaccination, or supplement use, including biotin. He was clinically euthyroid, and there was no evidence of Graves’ ophthalmopathy, tremor, atrial fibrillation, or a goiter. Serum anti-TPO antibody was raised (67.2 iu/mL, N<35.0). Lumbar puncture findings were normal and the cerebrospinal fluid anti-TPO antibody was not detected. Technetium99m uptake scan reported reduced uptake in both thyroid lobes, suggestive of thyroiditis. Hence, a diagnosis of triptorelin-induced thyroiditis was made. Upon discharge, his behaviour normalized and his TFT improved (TSH 0.02 mIU/L, fT4 32.3 pmol/L, fT3 6.7 pmol/L) without antithyroid drugs or glucocorticoids. During clinic review two months after he completed ADT, he was clinically euthyroid and his TFT had normalized (TSH 1.96m IU/L, fT4 12.0 pmol/L). CONCLUSION Patients with thyroid autoimmunity are more susceptible to thyroid dysfunction after GnRHa administration, probably due to GnRHa immunostimulatory actions, emphasizing need for TFT monitoring during GnRHa treatment. Those with persistent thyroid dysfunction after discontinuation of GnRHa therapy may require treatment.